Anxiety and Self-Actualization in Rainbow Rowell’s Fangirl: A Psychoanalytic and Humanistic Approach (Sastra Inggris UNPAM, 2025)
This study aims to analyze the anxiety disorder experienced by the main character in the novel Fangirl by Rainbow Rowell. The novel describes the journey of an introverted teenager named Cath who faces various challenges in college life, social relationships, and the process of self-discovery. The main focus of this research is how the symptoms of anxiety disorder are displayed in Cath's character and how environmental factors and past experiences affect her psychological condition. This study uses a literary psychology approach with anxiety disorder theory as the main foundation. The method used is descriptive qualitative analysis, with data collection techniques through in-depth reading and identification of anxiety signs in the narrative. The results show that Cath experiences various symptoms of anxiety disorder, such as excessive fear in social situations, a tendency to avoid interactions, and a negative mindset that affects her confidence. In addition, the novel also shows how support from family, friends, and writing activities can help Cath in dealing with her anxiety. This study contributes to the study of literary psychology and mental health studies in adolescent literature, by highlighting how anxiety disorders are represented in works of fiction.